Predicting probability of tolerating discrete amounts of peanut protein in allergic children using epitope‐specific IgE antibody profiling. Issue 10 (17th August 2022) - Suprun, Maria; Kearney, Paul; Hayward, Clive; Butler, Heather; Getts, Robert; Sicherer, Scott H.; Turner, Paul J.; Campbell, Dianne E.; Sampson, Hugh A.
Abstract: Background: IgE‐epitope profiling can accurately diagnose clinical peanut allergy. Objective: We sought to determine whether sequential (linear) epitope‐specific IgE (ses‐IgE) profiling can provide probabilities of tolerating discrete doses of peanut protein in allergic subjects undergoing double‐blind, placebo‐controlled food challenges utilizing PRACTALL dosing. Methods: Sixty four ses‐IgE antibodies were quantified in blood samples using a bead‐based epitope assay. A pair of ses‐IgEs that predicts Cumulative Tolerated Dose (CTD) was determined using regression in 75 subjects from the discovery cohort. This epitope‐based predictor was validated on 331 subjects from five independent cohorts (ages 4–25 years). Subjects were grouped based on their predicted values and probabilities of reactions at each CTD threshold were calculated. Results: In discovery, an algorithm using two ses‐IgE antibodies was correlated with CTDs (rho = 0.61, p  < .05); this correlation was 0.51 ( p  < .05) in validation. Using the ses‐IgE‐based predictor, subjects were assigned into "high, " "moderate, " or "low" dose‐reactivity groups. On average, subjects in the "high" group were four times more likely to tolerate a specific dose, compared with the "low" group. For example, predicted probabilities of tolerating 4, 14, 44, and 144 or 444 mg in the "low" group were 92%, 77%, 53%, 29%, and 10% compared with 98%, 95%, 94%, 88%, and 73% in the "high" group. Conclusions: Accurate predictions of food challenge thresholds are complex due to factors including limited responder sample sizes at each dose and variations in study‐specific challenge protocols. Despite these limitations, an epitope‐based predictor was able to accurately identify CTDs and may provide a useful surrogate for peanut challenges. Abstract : This study evaluates whether ses‐IgE profiling can predict probability of tolerating discrete doses of peanut protein in allergic subjects.There is a moderate negative correlation between the number of IgE epitopes and CTDs. The pair of ses‐IgE (Ara h 2_008 and Ara h 3_100) provide the best prediction of CRD. On average, subjects in the high‐dose reactivity group are 4 times more likely to tolerate a specific dose, compared to the low‐dose group.Abbreviations: CRD, cumulative reactive dose; CTD, cumulative tolerated dose; ses‐IgE, sequential (linear) epitope‐specific immunoglobulin E